1218. Activity of Meropenem-Vaborbactam and Comparator Agents Against Carbapenemase-Negative, Carbapenem-Resistant Enterobacterales from US Hospitals. (4th December 2021) - Castanheira, Mariana; Castanheira, Mariana; Doyle, Timothy B; Kantro, Valerie; Mendes, Rodrigo E; Shortridge, Dee
Abstract: Background: Meropenem-vaborbactam (MVB) is an important addition to the armamentarium to treat infections caused by carbapenem-resistant Enterobacterales (CREs). Carbapenemase-negative (CN) CRE isolates have been reported, but the activity of newer agents against these isolates is still not well understood. We evaluated the activity of MVB against CN-CRE collected during 6 years of surveillance in US hospitals. Methods: A total of 27, 968 Enterobacterales isolates collected in US hospitals from 2014-2019 were susceptibility tested by reference broth microdilution methods. Results were interpreted using CLSI 2020 breakpoints. CRE isolates were submitted to PCR/sequencing (2014-2015) or whole genome sequencing (WGS; 2016-2019) for characterization of carbapenemase genes. Isolates from 2016-2019 were evaluated for other beta-lactam resistance mechanisms. Results: Among 357 (1.3% of all isolates) CRE isolates identified during 6 years of surveillance, 48 (13.4% of the CRE) isolates did not produce known carbapenemases. The CN-CRE collection included 7 bacterial, species, or species complex. The top four most common species in the collection were K. pneumoniae (16 isolates) followed by E. cloacae (9), E. coli (8), and K. aerogenes (8). MVB was the most active agent tested against these isolates, inhibiting 47/48 (97.9%) of the isolates tested. The only isolate displaying a resistant MIC for MVB was a P. mirabilis (MIC, 16 mg/L) collected in 2015. Meropenem alone inhibited only 2.1% of the isolates. Other beta-lactams inhibited 4.2 to 14.6% of the isolates. Among non-beta-lactam comparator agents, tigecycline and amikacin inhibited 93.8 and 91.7% of the isolates, respectively, when applying CLSI or US FDA breakpoints. A total of 89.6% of the isolates had intermediate colistin MIC values. Among the 27 isolates collected from 2016-2019 that were submitted to WGS, 15 harbored CTX-M encoding genes. K. aerogenes and E. cloacae isolates (3 each) overexpressed AmpC. OmpC/K36 was disrupted in 20 isolates and OmpF/K35 was disrupted in 8 isolates. Conclusion: MVB displayed good activity against CN-CRE isolates from US hospitals. This combination agent could be a good option to treat infections caused by these isolates. Disclosures: Mariana Castanheira, PhD, AbbVie (formerly Allergan ) (Research Grant or Support)Bravos Biosciences (Research Grant or Support)Cidara Therapeutics, Inc. (Research Grant or Support)Cipla Therapeutics (Research Grant or Support)Cipla USA Inc. (Research Grant or Support)GlaxoSmithKline (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Melinta Therapeutics, LLC (Research Grant or Support)Pfizer, Inc. (Research Grant or Support)Qpex Biopharma (Research Grant or Support)Shionogi (Research Grant or Support)Spero Therapeutics (Research Grant or Support) Mariana Castanheira, PhD, Affinity Biosensors (Individual(s) Involved: Self): Research Grant or Support; Allergan (Individual(s) Involved: Self): Research Grant or Support; Amicrobe, Inc (Individual(s) Involved: Self): Research Grant or Support; Amplyx Pharma (Individual(s) Involved: Self): Research Grant or Support; Artugen Therapeutics USA, Inc. (Individual(s) Involved: Self): Research Grant or Support; Astellas (Individual(s) Involved: Self): Research Grant or Support; Basilea (Individual(s) Involved: Self): Research Grant or Support; Beth Israel Deaconess Medical Center (Individual(s) Involved: Self): Research Grant or Support; BIDMC (Individual(s) Involved: Self): Research Grant or Support; bioMerieux Inc. (Individual(s) Involved: Self): Research Grant or Support; BioVersys Ag (Individual(s) Involved: Self): Research Grant or Support; Bugworks (Individual(s) Involved: Self): Research Grant or Support; Cidara (Individual(s) Involved: Self): Research Grant or Support; Cipla (Individual(s) Involved: Self): Research Grant or Support; Contrafect (Individual(s) Involved: Self): Research Grant or Support; Cormedix (Individual(s) Involved: Self): Research Grant or Support; Crestone, Inc. (Individual(s) Involved: Self): Research Grant or Support; Curza (Individual(s) Involved: Self): Research Grant or Support; CXC7 (Individual(s) Involved: Self): Research Grant or Support; Entasis (Individual(s) Involved: Self): Research Grant or Support; Fedora Pharmaceutical (Individual(s) Involved: Self): Research Grant or Support; Fimbrion Therapeutics (Individual(s) Involved: Self): Research Grant or Support; Fox Chase (Individual(s) Involved: Self): Research Grant or Support; GlaxoSmithKline (Individual(s) Involved: Self): Research Grant or Support; Guardian Therapeutics (Individual(s) Involved: Self): Research Grant or Support; Hardy Diagnostics (Individual(s) Involved: Self): Research Grant or Support; IHMA (Individual(s) Involved: Self): Research Grant or Support; Janssen Research & Development (Individual(s) Involved: Self): Research Grant or Support; Johnson & Johnson (Individual(s) Involved: Self): Research Grant or Support; Kaleido Biosceinces (Individual(s) Involved: Self): Research Grant or Support; KBP Biosciences (Individual(s) Involved: Self): Research Grant or Support; Luminex (Individual(s) Involved: Self): Research Grant or Support; Matrivax (Individual(s) Involved: Self): Research Grant or Support; Mayo Clinic (Individual(s) Involved: Self): Research Grant or Support; Medpace (Individual(s) Involved: Self): Research Grant or Support; Meiji Seika Pharma Co., Ltd. (Individual(s) Involved: Self): Research Grant or Support; Melinta (Individual(s) Involved: Self): Research Grant or Support; Menarini (Individual(s) Involved: Self): Research Grant or Support; Merck (Individual(s) Involved: Self): Research Grant or Support; Meridian Bioscience Inc. (Individual(s) Involved: Self): Research Grant or Support; Micromyx (Individual(s) Involved: Self): Research Grant or Support; MicuRx (Individual(s) Involved: Self): Research Grant or Support; N8 Medical (Individual(s) Involved: Self): Research Grant or Support; Nabriva (Individual(s) Involved: Self): Research Grant or Support; National Institutes of Health (Individual(s) Involved: Self): Research Grant or Support; National University of Singapore (Individual(s) Involved: Self): Research Grant or Support; North Bristol NHS Trust (Individual(s) Involved: Self): Research Grant or Support; Novome Biotechnologies (Individual(s) Involved: Self): Research Grant or Support; Paratek (Individual(s) Involved: Self): Research Grant or Support; Pfizer (Individual(s) Involved: Self): Research Grant or Support; Prokaryotics Inc. (Individual(s) Involved: Self): Research Grant or Support; QPEX Biopharma (Individual(s) Involved: Self): Research Grant or Support; Rhode Island Hospital (Individual(s) Involved: Self): Research Grant or Support; RIHML (Individual(s) Involved: Self): Research Grant or Support; Roche (Individual(s) Involved: Self): Research Grant or Support; Roivant (Individual(s) Involved: Self): Research Grant or Support; Salvat (Individual(s) Involved: Self): Research Grant or Support; Scynexis (Individual(s) Involved: Self): Research Grant or Support; SeLux Diagnostics (Individual(s) Involved: Self): Research Grant or Support; Shionogi (Individual(s) Involved: Self): Research Grant or Support; Specific Diagnostics (Individual(s) Involved: Self): Research Grant or Support; Spero (Individual(s) Involved: Self): Research Grant or Support; SuperTrans Medical LT (Individual(s) Involved: Self): Research Grant or Support; T2 Biosystems (Individual(s) Involved: Self): Research Grant or Support; The University of Queensland (Individual(s) Involved: Self): Research Grant or Support; Thermo Fisher Scientific (Individual(s) Involved: Self): Research Grant or Support; Tufts Medical Center (Individual(s) Involved: Self): Research Grant or Support; Universite de Sherbrooke (Individual(s) Involved: Self): Research Grant or Support; University of Iowa (Individual(s) Involved: Self): Research Grant or Support; University of Iowa Hospitals and Clinics (Individual(s) Involved: Self): Research Grant or Support; University of Wisconsin (Individual(s) Involved: Self): Research Grant or Support; UNT System College of Pharmacy (Individual(s) Involved: Self): Research Grant or Support; URMC (Individual(s) Involved: Self): Research Grant or Support; UT Southwestern (Individual(s) Involved: Self): Research Grant or Support; VenatoRx (Individual(s) Involved: Self): Research Grant or Support; Viosera Therapeutics (Individual(s) Involved: Self): Research Grant or Support; Wayne State University (Individual(s) Involved: Self): Research Grant or Support Timothy B. Doyle, AbbVie (formerly Allergan ) (Research Grant or Support)Bravos Biosciences (Research Grant or Support)GlaxoSmithKline (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Pfizer, Inc. (Research Grant or Support)Shionogi (Research Grant or Support)Spero Therapeutics (Research Grant or Support) Valerie Kantro, n/a, Melinta Therapeutics, Inc. (Research Grant or Support) Rodrigo E. Mendes, PhD, AbbVie (Research Grant or Support)AbbVie (formerly Allergan ) (Research Grant or Support)Cipla Therapeutics (Research Grant or Support)Cipla USA Inc. (Research Grant or Support)ContraFect Corporation (Research Grant or Support)GlaxoSmithKline, LLC (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Melinta Therapeutics, LLC (Research Grant or Support)Nabriva Therapeutics (Research Grant or Support)Pfizer, Inc. (Research Grant or Support)Shionogi (Research Grant or Support)Spero Therapeutics (Research Grant or Support) Dee Shortridge, PhD, AbbVie (formerly Allergan ) (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Melinta Therapeutics, LLC (Research Grant or Support)Shionogi (Research Grant or Support)